2005
DOI: 10.1002/adsc.200505132
|View full text |Cite
|
Sign up to set email alerts
|

New Trends in Palladium‐Catalyzed Transfer Hydrogenations Using Formic Acid

Abstract: In the presence of a catalytic amount of organic bases, Pd-catalyzed transfer hydrogenations with formic acid were found to be facile processes. These new conditions produce innocuous carbon dioxide as the by-product compared to the use of ammonium formate, which generates ammonia and carbon dioxide as gaseous by-products which recombine to create unsafe conditions. When the substrate is basic enough to form salts with formic acid, no additional base is necessary. In certain cases, the product of the reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…On the basis of literature reports on transfer hydrogenations with FA promoted by a catalytic amounts of amines, 41 trioctylamine (TOA) was tested in our triphase system made by water/ioctane/[P 8,8,8,1 …”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…On the basis of literature reports on transfer hydrogenations with FA promoted by a catalytic amounts of amines, 41 trioctylamine (TOA) was tested in our triphase system made by water/ioctane/[P 8,8,8,1 …”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…2-butanol yield was 43% using 82 mmol of 2-butanone, , table 3). in literature was found that the use of formate salts is an interesting alternative as a hydrogen source, which generates non-gaseous by-products that can be easily recovered [30]. to date, the reactions related to the hydrogenation of 2-butanone in 2-butanol are still being studied to determine which are the factors and the optimal conditions to obtain a higher yield of the product.…”
Section: -Butanone Hydrogenation Into 2-butanol Preliminary Resultsmentioning
confidence: 99%
“…By considering the p K a of formic acid (3.5), the acid form (HCO 2 H) contributes to the reaction conversion better than basic formate (HCO 2 − ) does. H 2 transfer from formic acid to a nitro compound has often been facilitated in the presence of a base, such as triethylamine and NH 3 [28,32,4244]. Therefore, the addition of such bases is usually necessary for transfer hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…Because Pd-based catalysts have usually been regarded as the most active catalysts [2728 32], we modified the inner surface of tubular reactors with thin Pd, porous Pd, and their oxidized metal layers. Herein, we present a simple, rapid and convenient process for the reduction of p -nitrophenol, which is compatible with high reaction conversion under mild conditions.…”
Section: Introductionmentioning
confidence: 99%